Co-creating holistic injury prevention training for youth handball: Development of an intervention targeting end-users at the individual, team, and organizational levels - Ageberg, E.; Bunke, S.; Linnéll, J.; Moesch, K. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Interventions that are co-created with end-users, and that are informed by behavior change or implementation theories, support implementation in real world settings. However, injury prevention programs for youth athletes have typically been developed by experts with no, or insufficiently described, end-user involvement and without guidance by theories. The aim of the current study was to describe the development of a holistic injury prevention intervention for youth handball targeting end-users at different levels, through using knowledge from end-users and researchers/experts and applying relevant behavior change and implementation theories.